Toxicity of CuO and ZnO nanoparticles and their bulk counterparts on selected soil-borne fungi - Guerrero, Jonathan Jaime G.; Songkumarn, Pattavipha; U. Dalisay, Teresita; Pangga, Ireneo B.; Organo, Nolissa D. (Agriculture and Natural Resources, 2020)
The antifungal effects of copper oxide (CuO) and zinc oxide (ZnO) in bulk and nano forms were tested in vitro against important soil-borne fungi and one fungal-like oomycete. Potato dextrose agar amended with 500 parts per million (ppm), 1,000 ppm and 1,500 ppm and broth with 250 ppm of either metal oxide were inoculated with fungi aged 7 d. The percentage growth inhibition and biomass were measured after 7 d. Mycelial alterations and cell membrane damage were recorded using scanning electron microscopy and fluorescence microscopy. The results showed that most of the test fungi were susceptible to CuO in both forms rather than to ZnO. Exposure to CuO and ZnO resulted in shriveling of mycelia and possible damage to the cell membrane in Rhizoctonia solani, Sclerotium rolfsii and Fusarium oxysporum f. sp. lycopersici (Fol). Compound properties, not size, were the main cause of toxicity to the test fungi. Exposure and concentration were vital in the metal-oxide toxicity mechanism. It was recommended that a range of sizes be used and t